2021
DOI: 10.1002/uog.22165
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of motor function in patients who underwent prenatal or postnatal neural tube defect repair

Abstract: Objective To compare the evolution of motor function from mid‐gestation to 12 months of age between prenatally and postnatally repaired cases of open neural tube defect (ONTD). Methods This was a retrospective cohort study of all fetuses that underwent prenatal (fetoscopic or open hysterotomy) or postnatal ONTD repair at a single institution between November 2011 and December 2018. The anatomical level of the lesion was defined as the upper bony spinal defect at initial magnetic resonance imaging assessment. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
1
16
0
2
Order By: Relevance
“…Prior to surgery, all patients underwent comprehensive maternal health evaluation, fetal magnetic resonance imaging (MRI), fetal ultrasound examination and fetal echocardiography, a mental health evaluation, social circumstances assessment and a full multidisciplinary team consultation. A detailed description of the prenatal and postnatal imaging examinations and assessments performed, as well as management, is published elsewhere 7 .…”
Section: Methodsmentioning
confidence: 99%
“…Prior to surgery, all patients underwent comprehensive maternal health evaluation, fetal magnetic resonance imaging (MRI), fetal ultrasound examination and fetal echocardiography, a mental health evaluation, social circumstances assessment and a full multidisciplinary team consultation. A detailed description of the prenatal and postnatal imaging examinations and assessments performed, as well as management, is published elsewhere 7 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that intrauterine damage of the nervous system is progressive. 44 The "two-hit hypothesis" suggests that an initial lesion occurs, the anatomical defect itself, and then a second lesion due to the ongoing exposure of the nervous tissue to amniotic fluid. [45][46][47] Therefore, based on the hypothesis that an early defect closure may be associated with improved postnatal outcomes by reducing exposure of the neural tissue to amniotic fluid for a prolonged time, the concept of prenatal repair was introduced.…”
Section: Postnatal Surgery or Fetal Surgerymentioning
confidence: 99%
“…[45][46][47] Therefore, based on the hypothesis that an early defect closure may be associated with improved postnatal outcomes by reducing exposure of the neural tissue to amniotic fluid for a prolonged time, the concept of prenatal repair was introduced. 3,44,46 In 2011, the MOMS trial was published, which compared the outcomes of open prenatal surgery and postnatal surgery. 3 The study was ended early due to the clear benefits observed in the prenatal surgery group, which showed, at the 12-month follow-up, a reduction in VPS requirement (40 % in the prenatal versus 82 % in the postnatal surgery group; relative risk [RR] = 0.48; 97.7 % confidence interval [CI]: 0.36-0.64; p < 0.001) and, at the 30-month followup, an improved composite outcome of mental development and motor function.…”
Section: Postnatal Surgery or Fetal Surgerymentioning
confidence: 99%
“…Se ha demostrado que el daño intraútero del sistema nervioso es progresivo. 44 La "teoría de los 2 golpes" sugiere que hay una primera lesión, el defecto anatómico en sí, y luego una segunda, dada por la continua exposición del tejido nervioso al líquido amniótico. [45][46][47] Por ello, con la hipótesis de que el cierre precoz del defecto podría asociarse a mejores resultados posnatales al disminuir la exposición del tejido neural al líquido amniótico durante un período prolongado, se introdujo el concepto de la corrección prenatal.…”
Section: Cirugía Posnatal O Cirugía Fetalunclassified
“…[45][46][47] Por ello, con la hipótesis de que el cierre precoz del defecto podría asociarse a mejores resultados posnatales al disminuir la exposición del tejido neural al líquido amniótico durante un período prolongado, se introdujo el concepto de la corrección prenatal. 3,44,46 E n e l a ñ o 2 0 1 1 , s e p u b l i c ó e l M O M S , el cual comparó los resultados de la cirugía prenatal abierta con la posnatal. 3 El estudio fue interrumpido precozmente debido a los claros beneficios en la rama de la cirugía prenatal, que mostró, en el seguimiento a 12 meses, una reducción de la necesidad de colocación de DVP (el 40 % en el grupo de cirugía prenatal vs. el 82 % en el grupo posnatal; riesgo relativo -RR-= 0,48; intervalo de confianza -IC-del 97,7 %: 0,36-0,64; p < 0,001) y, en el seguimiento a 30 meses, una mejoría en el resultado compuesto de desarrollo mental y función motora.…”
Section: Cirugía Posnatal O Cirugía Fetalunclassified